Magnetic susceptibility of sediment core LMAHA-18 from lake Mahasarika, northern Madagascar - Vincent Montade; Hermann Behling; Laurent Bremond; Sylvie Rouland; Gerhard Daut; Thomas Kasper; Charly Favier (PANGAEA, 2024)
The datasets provided here correspond to sedimentary charcoal counts, magnetic susceptibility measurements, and δ13C isotopic measurements obtained from a lacustrine sediment core recovered from Lake Maharasika in Montagne d extquotesingleAmbre (northern Madagascar, 1,073 m asl). Fieldwork has been carried out in August 2018. The sediment core LMAHA-18 was taken from the central and deepest part of the lake (7 m water depth; 12.53509S, 49.17701E). Core LMAHA-18 was sampled with a Livingstone piston sediment corer operated from a small platform settled on two rubber boats. Using sampling tubes of ca. 5 cm diameter and 120 cm length, a total of 6 sections of about 100 cm sediment length were sampled with overlaps of 10-50 cm length. Preserved in aluminium tubes for transport to the laboratory, sediment was extruded from each aluminium tube and split into two sister cores, LMAHA-18a and LMAHA-18b. Each sister core was stored under cool (4°C) and dark conditions at the laboratory facilities (LMAHA-18a at the Friedrich-Schiller-University Jena and LMAHA-18b at the University of Goettingen, Germany). For magnetic susceptibility measurements, the core was scanned in 3 mm steps with three replicate measurements using an MS2E surface scanning sensor (Bartington Instruments).